2013
DOI: 10.1080/13603116.2011.602525
|View full text |Cite
|
Sign up to set email alerts
|

Supporting inclusion of at risk students in secondary school through positive behaviour support

Abstract: The retention of 'at risk' students in secondary schools is a major challenge to inclusive education policy. Students with non-compliant behaviour at this level are typically dealt with by authoritarian and punitive disciplinary systems that frequently lead to exclusion from school. This paper reports on the successful establishment of a positive behaviour support system in a secondary school. School-wide systemic change was developed to support the inclusion of students at risk of failure and suspension for n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…Specifically, in studies of focused goal setting, students were more likely to attain their goals when they were involved directly in setting those goals (Barbrack & Maher, 1984;Hill & Brown, 2013;Maher, 1981). In these three studies, students also reported strong buy-in to the procedures, which indicates that not only does allowing students to provide input about their goals result in positive perceptions about intervention, but also positive student outcomes.…”
Section: Independent Variable and Outcomesmentioning
confidence: 96%
See 2 more Smart Citations
“…Specifically, in studies of focused goal setting, students were more likely to attain their goals when they were involved directly in setting those goals (Barbrack & Maher, 1984;Hill & Brown, 2013;Maher, 1981). In these three studies, students also reported strong buy-in to the procedures, which indicates that not only does allowing students to provide input about their goals result in positive perceptions about intervention, but also positive student outcomes.…”
Section: Independent Variable and Outcomesmentioning
confidence: 96%
“…In these four studies, the primary purpose was to evaluate the effects of goal setting on student outcomes (Barbrack & Maher, 1984;Hill & Brown, 2013;Maher, 1981;Mazzotti et al, 2013). In all four studies, some students had input about their goal, and in two studies, some students did not have input about their goal.…”
Section: Focused Goal Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…Graham and Harwood 2011;Razer, Friedman, and Warshofsky 2013;Persson 2013;Hill and Brown, 2013;Cefai, Cooper, and Vella 2013). Across different settings, contexts and population groups, these and others document the understandings, mechanisms and practices which move schools towards being able to provide support and an inclusive environment for all students.…”
Section: Enabling Spacesmentioning
confidence: 99%
“…Leading researchers in the academic field define goal setting in similar ways. Goals in academia need to be specific and monitored as well as include feedback during the attainment process by an outside source (Moore, Prebble, Robertson, Watford, & Anderson, ) . Current goal setting research in the education field is centered in the kindergarten through the twelfth‐grade level and is mostly focused on behavioral issues in the classroom.…”
Section: Definition and Uses Of The Conceptmentioning
confidence: 99%